Restorative Justice as a Resolution Mechanism for Petty Theft: A Comparative Legal Review of New Zealand and Malaysia - Santoso, Bambang; Kurniawan, Itok Dwi; Sukma, Dara Pustika; Pati, Umi Khaerah; Mohamad, Mohamad Hanapi Bin (Universitas Negeri Semarang, 2025)
Petty theft is one of the most common criminal offenses and contributes to prison overcrowding, even though the losses involved are minimal and often committed by economically vulnerable individuals. The retributive criminal justice system in Indonesia has proven less effective in resolving such cases fairly and efficiently. This study aims to analyze the optimization of restorative justice in handling petty theft cases in Indonesia, while comparing its application with Malaysia and New Zealand. The research employs a normative juridical method, using statutory and comparative legal approaches. The research shows that Indonesia has introduced restorative justice through the Attorney General's Regulation Number 15 of 2020. However, practical implementation faces challenges, including limited awareness among law enforcement, insufficient institutional synergy, and a lack of supporting facilities. In Malaysia, restorative principles are reflected in local practices, although not formally adopted in national legal frameworks. In contrast, New Zealand has institutionalized restorative justice, especially in youth cases, with comprehensive procedures and strong community participation. The comparative analysis suggests that successful implementation depends on regulatory clarity, trained human resources, and active community involvement. Indonesia must therefore enhance its legal infrastructure and cross-sector collaboration to ensure that restorative justice becomes an effective tool in resolving petty theft cases.